An evaluation of the population uptake and contact tracer utilisation of the Covid-19 Bluetooth Exposure Notification Framework in New Zealand - Tim Chambers; Andrew Anglemyer; Andrew Chen; June Atkinson; Phoebe Elers; Michael G. Baker (Australian and New Zealand Journal of Public Health)
Objective: Our primary research objective was to assess the population uptake and contact tracer utilisation of the Bluetooth function of the New Zealand Covid Tracer App (NZCTA) throughout the pandemic. Methods: We adopted a retrospective cohort study design using all diagnosed COVID-19 community cases from December 12, 2020 to February 16, 2022. Results: At its height, more than 60% of the eligible population had the Bluetooth function of NZCTA activated. However, only an estimated 2.2% of the population was able to fully participate. Cases managed by the national case investigation service were 17 times (aRR 17.54, 95%CI: 13.02-23.90) and 9 times (aRR 9.27, 95%CI: 6.91, 12.76) more likely to generate a Bluetooth token than cases managed by local public health units during the Delta and Omicron periods, respectively. Conclusions: The Bluetooth functionality of the NZCTA likely had a low impact on the pandemic response in NZ despite its exceptionally high levels of public uptake. The primary reason for the lack of impact was the low utilisation by contact tracers. Implications for public health: The results highlight the need for greater consultation and collaboration with the public health sector during the development and implementation of digital contact tracing tools.